2014
DOI: 10.1111/epi.12686
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of some statins on epileptogenesis and depressive‐like behavior in WAG/Rij rats, a genetic animal model of absence epilepsy

Abstract: SUMMARYObjective: Statins (3-hydroxy-3-methylglutaryl-coenzyme A [HMG-CoA] reductase inhibitors) exert cholesterol-independent pleiotropic effects that include antithrombotic, antiinflammatory, and antioxidative properties. Moreover, both in vitro and in vivo studies have shown neuroprotective, antiseizure, and antiexcitotoxic effects of statins, suggesting their potential role in the treatment of neurologic diseases. Only a few studies have investigated whether statins modulate absence seizure activity and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 49 publications
(169 reference statements)
1
58
0
2
Order By: Relevance
“…The studies of lovastatin and its analogs have been reported in several seizure models including audiogenic models in rodent and several observational studies in human (Banach et al 2014; Citraro et al 2014; Russo et al 2013; Scicchitano et al 2015). While the efficacy of seizure suppression varies from study to study, the anticonvulsant effect has been documented for lovastatin and other analogs.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of lovastatin and its analogs have been reported in several seizure models including audiogenic models in rodent and several observational studies in human (Banach et al 2014; Citraro et al 2014; Russo et al 2013; Scicchitano et al 2015). While the efficacy of seizure suppression varies from study to study, the anticonvulsant effect has been documented for lovastatin and other analogs.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, animals were weighed weekly every Monday between 9:00 and 11:00. Furthermore, particular attention was paid to the possible appearance of any obvious drug induced side-effects [47].…”
Section: For Subchronic Treatmentmentioning
confidence: 99%
“…As HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase inhibitors, statins can effectively decrease blood cholesterol levels 8 . Recently, SMV has been reported to show some cholesterol-independent effects that include anti-inflammatory, anti-oxidative and neuro-protective properties 9 .…”
Section: Introductionmentioning
confidence: 99%